Associations of autozygosity with a broad range of human phenotypes - Clark, David; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; Jonas, Jost B.; März, Winfried (Nature Communications, 2019)
In many species, the offspring of related parents suffer reduced reproductive success, a phenomenon known as inbreeding depression. In humans, the importance of this effect has remained unclear, partly because reproduction between close relatives is both rare and frequently associated with confounding social factors. Here, using genomic inbreeding coefficients (FROH) for >1.4 million individuals, we show that FROH is significantly associated (p < 0.0005) with apparently deleterious changes in 32 out of 100 traits analysed. These changes are associated with runs of homozygosity (ROH), but not with common variant homozygosity, suggesting that genetic variants associated with inbreeding depression are predominantly rare. The effect on fertility is striking: FROH equivalent to the offspring of first cousins is associated with a 55% decrease [95% CI 44–66%] in the odds of having children. Finally, the effects of FROH are confirmed within full-sibling pairs, where the variation in FROH is independent of all environmental confounding.
Gesehen am 28.02.2020
*Et al.: Marcus E. Kleber, Graciela E. Delgado, Bernhard K. Krämer, Jost B. Jonas, Winfried März [und 430 weitere Personen]